A criminalidade e o desenvolvimento das microrregiões no estado de Mato Grosso - Delgado, Hozano José (2016)
The rising crime has been approached as a serious and complex social problem. The usual measures to combat crime, by itself, have not been sufficient to effectively contain this evil in some regions. This is even worse if, at the analyzed site, permeates illicit drugs, organized crime, terrorism, fragile institutions and transnational relations of the crime. The literature on development and crime evidences a strong relationship between development and crime. As a complement, the microeconomic theory that highlights the causes and determinants of crime helps to establish the relationship among the analyzed variables. This study investigates the relationship between development and crime in Mato Grosso micro regions through an econometric analysis. The murder data as a crime indicator and the Firjan Index of Municipal Development (FIMD) as a development indicator, together were used to estimate a panel data regression for the period 2006-2013. It was expected that the high crime in the State should be related to the low development of micro-regions, as well as micro-regions with high development indicators showed low crime. Among the main results, it is emphasized that crime does not affect the FIMD indicator, but affects the quality of life, ie, affects the economic development, which confirms the initial hypothesis that high crime negatively impacts the development of micro-regions. Conversely, the development affects crime. It follows also that the FIMD indicator has serious limitations as a development indicator. And finally, although the State has provided positive results in the growth of their wealth, it has serious social problems impacting directly in its development.